2015
DOI: 10.1007/s12161-015-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fatty Acids in Beef by Liquid Chromatography-Electrospray Ionization Tandem Mass Spectrometry

Abstract: A method was developed to separate, identify, and quantify 28 fatty acids of potential health relevance using liquid chromatography/electrospray ionizationmass spectrometry (LC/ESI-MS). Optimization of the experimental factors enabled baseline separation of the fatty acids including three pairs of closely related fatty acid isomers (C18:3n-3 and C18:3n-6; C18:1 and C18:1 t; and C20:3n-3 and C20:3n-6) that are challenging to separate. The limits of detection ranged from 0.01 to 0.26 mg L −1 for the 28 fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Reversed-phase chromatography and mixed-mode chromatography have been the traditional choices for separation and screening of underivatized medium-to long-chain fatty acids in LC-MS due to their low polarity nature [25,27,28]. However, their derivatization to less polar species helps to enhance screening coverage in LC-MS-based applications that require separation of metabolites with wide range of polarities [29,30].…”
Section: Untargeted Screening Of Derivatized Carboxylic Acids Using H...mentioning
confidence: 99%
“…Reversed-phase chromatography and mixed-mode chromatography have been the traditional choices for separation and screening of underivatized medium-to long-chain fatty acids in LC-MS due to their low polarity nature [25,27,28]. However, their derivatization to less polar species helps to enhance screening coverage in LC-MS-based applications that require separation of metabolites with wide range of polarities [29,30].…”
Section: Untargeted Screening Of Derivatized Carboxylic Acids Using H...mentioning
confidence: 99%
“…Only a few studies were reported on baseline separation of isomers such as a-linolenic acid (18:3n À 3) and g-linolenic acid (18:3n À 6) by using LC; moreover, total separation requires either long analysis under isocratic conditions 24 and/or use of a chiral stationary phase. 25 The developed method allowed separation of some fatty acids commonly found in human plasma, where 23 fatty acids were identied with oleic acid being the most abundant fatty acid found in plasma and cells.…”
Section: Untargeted Screening Of Carboxylic Acids By Using Hr-msmentioning
confidence: 99%
“…A popular method of FA analysis is the derivatization of FAs into fatty acid methyl esters (FAME) [18]. MS methods for the analysis of lipids have also been developed for high performance and ultra high performance liquid chromatography HPLC/UHPLC-MS [8,[19][20][21][22] and supercritical fluid chromatography SFC-MS [2]. Many of these methods utilize tandem mass spectrometric techniques (MS/MS) to enhance both sensitivity and selectivity as well as increase the amount of structural information that can be obtained during analysis [15].…”
Section: Introductionmentioning
confidence: 99%